Amphorae from Vigna Marini-Vitalini, Caere, Italy - Scalici , Michele (Rei Cretariae Romanae Fautorum Acta, 2017)
The city of Caere, modern day Cerveteri, about 40 km NorthWest of Rome, is one of the main settlements of southern Etruria. Known above all for its Orientalizing period, the city played an important role also in the Archaic and Classical periods. Between 273 and 271 BC, Caere became officially part of the Roman state with the status of praefectura. The site known as the “Hypogeum of Clepsina” dates to that period and is currently being studied by a team of Queen’s University. Scholars have thus far agreed that the site offers limited evidence of the Roman period. Nevertheless, there are monuments of this period still clearly visible in the city’s topography, such as the theatre and the amphitheatre, and works of exceptional importance were found there, such as the Julio-Claudian statuary cycle. For this reason the excavations carried out by the University of Perugia between 2001–2003 and especially by the Queen’s University in 2012–2014 can give an important contribution to the knowledge of the history of the city after the 4th century BC.